Ethanol Preference and Drinking Behavior Are Controlled by RNA Editing in the Nucleus Accumbens - Shirahase, Takahira; Watanabe, Yoshihisa; Tsujimura, Atsushi; Kwak, Shin; Yamamoto, Toshiro; Kanamura, Narisato; Tanaka, Masaki (Frontiers in Behavioral Neuroscience, 2019)
RNA editing plays critical roles in normal brain function, and alteration of its activity causes various disorders. We previously found that chronic consumption of ethanol was associated with increased levels of RNA editing of serotonin 2C receptor in the nucleus accumbens (NAc). However, it remains unknown whether RNA editing in the NAc modulates alcohol addiction through the brain reward system. To investigate the involvement of NAc RNA editing in alcohol addiction, we generated NAc-specific knockout mice of the double-stranded RNA-specific adenosine deaminase ADAR2 using AAV-GFP/Cre and conducted a battery of behavioral tests including anxiety- and depression-like behaviors. In addition, NAc-specific ADAR2 knockout mice were exposed to ethanol vapor for 20 days, followed by ethanol-drinking and conditioned place preference tests. NAc-specific ADAR2 knockout mice showed a significant decrease in locomotor activity in the open field test although they did not develop anxiety- and depression-like behaviors. In addition, the enhancements of ethanol intake and ethanol preference that are usually observed after chronic ethanol vapor exposure were significantly reduced in these mice. These results suggest that ADAR2-mediated RNA editing in the NAc is involved in determination of alcohol preference after chronic alcohol consumption.